ANTESEDEN PEMBENTUK KEPUASAN KONSUMEN (STUDI PADA KONSUMEN TAS RUMAH WARNA YOGYAKARTA) - Khalifah Nurjannah; Fitroh Adhilla (Jurnal Fokus Manajemen Bisnis, 2019)
This study aims to determine the effect of the three forming factors consumer satisfaction consisting of product quality, brand image and price affect consumer satisfaction Rumah Yogyakarta bag colors both partial or simultaneous. This research is a quantitative research. Sampling with non probability sampling with purposive sampling technique that has criteria is a consumer of the Yogyakarta Color House bag female, have bought and used a Rumah Warna bag, and are> 18 years old year. Data collection in this study uses deployment questionnaire to be tested for validity and reliability, for data analysis using multiple regression analysis, t test, f test and R square. Subject this research is the consumers of Rumah Warna Yogyakarta bag already once bought and used a Rumah Color bag. The results showed that: 1) the quality of the product on the bag Rumah Warna does not have a significant effect on bag customer satisfaction Rumah Warna Yogyakarta, 2) brand image on Rumah Warna bag is influentialsignificant positive effect on customer satisfaction Rumah Warna Yogyakarta bag, 3) the price on the Rumah Warna bag has a significant positive effect on satisfaction Yogyakarta Rumah Color bag consumers, and 4) together quality product, brand image and price have a significant positive effect on satisfaction Yogyakarta Rumah Color bag consumers with an f test result of 0,000 <0.05, with a regression equation Y = 0.237 + 0.218 X1 + 0.337 X2 + 0.396 X3 + e. R Square of 0.496 or 49.6% which influences and the remaining 50.4% influenced by other variables not examined by this study.